A training module for the international course on plant genetic resources and genebank management: Held at the Rural Development Administration, Suwon, Republic of Korea on 7-18 September 2009 - Bioversity International; Rural Development Administration (2009)
This training module aims to train genebank curators and genetic resource professionals in good practices for effective ex situ conservation and genetic diversity held in genebanks. It was developed for a face-to-face short course on Genebank Management held at RDA Korea in 2009 and 2010. It includes lecture materials and pratical hands-on lab excercises.In particular it aims to:• enhance the use of standard protocols for routine genebank operations including how to develop a genebank operation manual• develop a practical understanding of the utilization of genetic resources and the interface between genebanks and breeders• equip participants with essential knowledge in documentation and database management• acquaint the participants with morphological and molecular techniques to characterize and evaluate plant genetic resources• enhance awareness of international and national policy instruments and regimes concerning access to and exchange of genetic resources